Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/504753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Encoding of wind direction by central neurons inDrosophila

Abstract: Wind is a major navigational cue for insects, but how wind direction is decoded by central neurons in the insect brain is unknown. Here, we find that walking flies combine signals from both antennae to orient to wind during olfactory search behavior. Movements of single antennae are ambiguous with respect to wind direction, but the difference between left and right antennal displacements yields a linear code for wind direction in azimuth. Second-order mechanosensory neurons share the ambiguous responses of sin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Wind perception is crucial for navigation, including anemotaxis (following odors upwind) or flight in general. The LH receives projections from the wedge, a third-order mechanosensory region [ 8 , 14 , 74 , 75 , 76 ] ( Figure S6 A). Genetic activation of WEDPN1 (R37E08-GAL4) generates increased wing-flick motion and differential wing-angling [ 77 ] ( Figure S6 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind perception is crucial for navigation, including anemotaxis (following odors upwind) or flight in general. The LH receives projections from the wedge, a third-order mechanosensory region [ 8 , 14 , 74 , 75 , 76 ] ( Figure S6 A). Genetic activation of WEDPN1 (R37E08-GAL4) generates increased wing-flick motion and differential wing-angling [ 77 ] ( Figure S6 C).…”
Section: Discussionmentioning
confidence: 99%
“…All belonged to GABAergic lineages [ 25 ]. A further ∼10 neurons from the wedge brushed past the LH, including previously studied wind-sensitive WEDPNs [ 76 ]. We found that all types except type 7 had an axon in the LH and dendrites in the wedge, with spill-over into other ill-defined third-order mechanosensory neuropils in the inferior region of the ventrolateral protocerebrum ( Figure 6 D).…”
Section: Methodsmentioning
confidence: 99%
“…In Drosophila , the wedge receives direct input from antennal mechanosensory neurons and input from secondary neurons of the antennal mechanosensory and motor center (Ito et al, ). Patch‐clamp recordings showed that wedge neurons in Drosophila are sensitive to wind direction by integrating mechanosensory input from both antennae (Suver et al, ). Extracellular recordings in the cockroach Blaberus suggest that CX neurons receive prominent mechanosensory input from the antennae, but whether these responses, likewise, reflect spatial tactile information, remains to be seen (Ritzmann, Ridgel, & Pollak, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study advances our understanding of the breadth of behaviors that are influenced by the JONs. The JO-C/E neurons were previously implicated in such behaviors as wind-induced suppression of locomotion, wind-guided orientation, gravitaxis, flight, and antennal grooming ( Hampel et al, 2015 ; Kamikouchi et al, 2009 ; Mamiya and Dickinson, 2015 ; Suver et al, 2019 ; Yorozu et al, 2009 ). Our finding that optogenetic activation of the JO-C/E neurons results in wing flapping ( Figure 6B,C,D ) is intriguing, given that these neurons were previously shown to detect wing beats and then modulate wing movements during flight ( Mamiya and Dickinson, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subpopulations of JONs are selectively excited by different vibrational frequencies or by sustained displacements of the antennae and send their projections into discrete zones in the CNS ( Kamikouchi et al, 2006 ). In accordance with their diverse physiological tuning properties, the JONs are implicated in controlling diverse behaviors including courtship, locomotion, gravitaxis, wind-guided orientation, escape, flight, and grooming ( Hampel et al, 2015 ; Kamikouchi et al, 2009 ; Lehnert et al, 2013 ; Mamiya et al, 2011 ; Mamiya and Dickinson, 2015 ; Suver et al, 2019 ; Tootoonian et al, 2012 ; Vaughan et al, 2014 ; Yorozu et al, 2009 ). However, efforts to define how the different JONs interface with downstream neural circuitry to influence these behaviors have been hampered by the incomplete description of the morphologically heterogeneous JON types within each subpopulation ( Kamikouchi et al, 2006 ; Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%